2008
DOI: 10.3354/meps07705
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and connectivity remain high in eelgrass Zostera marina populations in the Wadden Sea, despite major impacts

Abstract: Beginning in the 1930s, eelgrass meadows declined throughout the Wadden Sea, leaving populations susceptible to extinction through patchiness, low density and isolation. Additional anthropogenic impacts have altered current regimes, nutrients and turbidity -al l of which affect eelgrass. Recent abiotic modeling studies suggest that poor recovery is the result of a regime shift caused by the loss of positive feedbacks between seagrass meadows and their capacity to mediate turbidity. Additionally, it is hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
1
20
1
Order By: Relevance
“…Similarly, Kornmann and Sahling (1977) also inferred that H. elongata, stranded on Helgoland in late summer, probably comes from sources in the British Channel because this seaweed often harbors algal epiphytes that are common in Brittany and southern England. The import of floating seaweed from the British Channel is likely supported by a strong coastal current that is also responsible for intensive gene flow among populations of eelgrass Zostera marina along the Wadden Sea coast (Ferber et al, 2008). The seasonal variations of floating seaweed abundances in the German Bight were similar to those reported from other regions (Thiel and Gutow, 2005a).…”
Section: Floating Seaweedsupporting
confidence: 71%
“…Similarly, Kornmann and Sahling (1977) also inferred that H. elongata, stranded on Helgoland in late summer, probably comes from sources in the British Channel because this seaweed often harbors algal epiphytes that are common in Brittany and southern England. The import of floating seaweed from the British Channel is likely supported by a strong coastal current that is also responsible for intensive gene flow among populations of eelgrass Zostera marina along the Wadden Sea coast (Ferber et al, 2008). The seasonal variations of floating seaweed abundances in the German Bight were similar to those reported from other regions (Thiel and Gutow, 2005a).…”
Section: Floating Seaweedsupporting
confidence: 71%
“…However, recent information strongly suggests that resilience is linked with genetic diversity (Reusch 2001;Williams 2001;Hufford and Mazer 2003;Reusch et al 2005;Ehlers et al 2008;Ferber et al 2008), and the potential for gene flow among eelgrass populations should be a consideration in planning for the long-term success of eelgrass restoration efforts. In the systems that we studied, low levels of flowering may constrain gene flow even within a discrete patch.…”
Section: Multiple Stressors and Stable Statesmentioning
confidence: 98%
“…However, the relationship between high or low drifting potential and genetic connectivity between the seagrass populations is not always straightforward (Waycott et al 2006). For example, Zostera marina has been shown to disperse on the order of 100 km by dislodged fruit-bearing rhipidia (Harwell & Orth 2002, Källström et al 2008, and populations showed high genetic connectivity at an oceanic scale (Reusch 2002, Muñiz-Salazar et al 2005, Ferber et al 2008), a phenomenon also found for Zostera noltii ). Contrary to this, Posidonia oceanica has low genetic migration rates, and a clear E-W genetic division was found in the Mediterranean ).…”
Section: Introductionmentioning
confidence: 99%